Die christlichen und antichristlichen Elemente in der Musik von Black Sabbath (1970-1973) - Efthimiou, Charris (Muzikološki zbornik, 2014)
Were the members of BLACK SABBATH actually worshipers of the devil? Did they actually want to insult Christianity with their new sound? The aim of this paper is to find concrete answers to these questions mentioned. A further aim is to examine from a music analytical point of view the songs of this band (from 1970 to 1973), which have a religious background.
Keywords: analiza glasbe; Black Sabbath; glasbene skupine; religija; religion